A STATISTICAL APPROACH TO THE INVESTIGATION OF MAGNETIC PROPERTIES OF MAIN SEQUENCE STARS - Monin, D. N.; Fabrika, S. N.; Valyavin, G. G. (Одеські астрономічні публікації, 2017)
The results of a systematic magnetic survey of the brightest northern MS stars are presented. A homogeneous and representative sample of 30 upper MS stars was observed. Both fast and slow rotating normal and CP stars have been investigated by the same technique. A limit in accuracy of magnetic field measurements at a level of 10 G was reached for the stars with sharp lines in spectra. A statistical analysis of the magnetic field strength distribution of MS stars have been made. In the surface magnetic field range, BS = 0.1 ÷ 100 kG, the distribution cannot be represented by a single power relation. There is a real break at BS ≈ 3 - 5 kG earlier suspected, and which cannot be explained by observational selections only. We discuss a possible mechanism of the break. The distribution of highly magnetic stars is represented by a power law. It was shown that normalization of the high-field part of the distribution could be obtained in the study of the low-field part where the probabilities of finding are much higher. The distribution of weakly magnetic stars is It is very similar to that of magnetic white dwarfs. It has been determined that there are 7.2÷8.7% of MS stars with surface magnetic fields higher than 1 kG among MS stars of B8÷F9 spectral classes.